Do firms operating in a shared institutional environment have similar sustainability disclosure practices? A comparative analysis of multinational and locally listed firms in Africa - Emmanuel Kofi Penney; Anthony Owusu-Ansah; Godfred Amewu; Randolph Nsor-Ambala (Cogent Business & Management, 2023)
This study compares the quality of Corporate Social Responsibility (CSR) practices and reporting of firms operating in Africa listed in Western economies and firms exclusively listed on the African stock exchange, using the Global Reporting Initiative (GRI) CSR checklist. Interpretive content analysis was conducted on the website publications and relevant reports of 135 firms listed on African stock exchanges. Non-parametric(Mann-Whitney U and Cohen d test) analyses were applied to check for significant differences between the mean scores of Western-listed firms and locally listed firms operating in African countries. The study's findings indicate (1) a Low CSR disclosure rate and (2) no significant CSR disclosure difference between exclusively African market-listed firms and multinationals. Multinationals do not lead in sustainability reporting. The finding of this study is a proposal for emerging economies to strengthen institutions and make them independent. The findings further encourage regulators and policymakers to question, with utmost importance, why the sophisticated propitious sustainability initiatives and reporting of Western economies are not practised in the developing world. Unlike previous studies, the current research uses Institutional Theory to compare CSR disclosure tendencies of environmentally Sensitive Industries (ESI) in which environmental policies seemingly make sustainability reporting quasi-mandatory.
Keywords: 650; CSR; disclosures; reporting; sub-Saharan Africa; Sustainability; sustainability reporting